Assessing Challenges in Vegetable Farming: A Comparative Study of Municipalities in Surkhet, Nepal - Vasishtha , Veetihotra (Journal of Entrepreneurship & Management Studies, 2025)
Vegetable farming plays a pivotal role in Nepal’s rural economy, particularly in Surkhet District, which serves as a significant agricultural hub. Despite its potential to enhance food security and rural incomes, the sector faces multifaceted challenges that vary across different municipalities. This study investigates these barriers by conducting a comparative analysis across five municipalities Birendranagar, Barahatal Rural, Panchhapuri, Gurvakot, and Bheriganga. Although prior studies have explored agricultural challenges at regional or national levels, there is a notable gap in understanding the municipality-level dynamics within Surkhet. Addressing this, the research employs a descriptive quantitative design using structured questionnaires administered to 228 vegetable farmers. Disproportionate stratified sampling ensured adequate representation from each municipality. The study identifies key production, financial, environmental, institutional, and infrastructural constraints and uses chi-square tests to evaluate differences in challenge prevalence across locations. Results reveal significant spatial disparities, indicating that urban and rural farmers encounter distinct issues shaped by infrastructure, geography, and market access. These findings carry important policy implications. Tailored interventions (such as improved irrigation in Bheriganga, pest management support in Barahatal, and better market infrastructure in Panchhapuri) can strengthen the sustainability of vegetable farming. Moreover, the research emphasizes the need for localized agricultural support services and climate-resilient farming strategies. By highlighting intra-district variations, the study contributes to more targeted and effective rural development policies in Karnali Province, supporting Nepal’s broader goals of economic resilience and agricultural modernization.